Quasiturbine rotor development optimization - Mohammed, Mohammed Akram (2014)
The Quasiturbine compressor is still in developing level and its have more advantages if compare with wankel and reciprocating compressors. Quasiturbine was separated in two main important components which they are housing and rotor .Quasiturbine rotor contains a number of parts such as blades, seal, support plate and mechanism .This research focus on modeling and simulation for Quasiturbine seal to improve it and reduce the wear by using motion analysis tool and simulation tool box in Solidworks 2014 software .This study has simulated the existing design and proposed design of seal with use Aluminum (1060 alloy ) as a material of seal for both cases . In addition it has been simulated three different materials for the proposed design of seal (Aluminum, ductile iron , steel ) .The proposed design of seal was selected as better design than the existing one when compared the distribution of von Mises stress and the percentage of deformation for both cases . According to the results of the three mateials that tested by simulation for the proposed design , ductile iron is the most suitable materials from the three tested materials for Quasiturbine seal .